Pengaruh Kepemimpinan Transformatif Dan Pelatihan Terhadap Pengembangan Kompetensi Karyawan Di Industri Hospitality - Fenny Sengkey (Universitas Triatma Mulya, 2024)
Hospitality is part of the tourism business that provides various forms of services that are managed commercially. Good service certainly requires training for employees at the hotel. Training is provided in order to improve the quality of work of each employee. The main problems in this study are: (a) does leadership have a significant effect on employee performance? (b) Does training have a significant effect on employee performance? (c) how do leadership and training simultaneously affect employee performance? This study is a survey study with a research instrument using a questionnaire. The analysis technique was carried out using a statistical regression approach and using a double log model. With a total of 102 respondents consisting of 67 men and 35 women. So that it is obtained that leadership has a positive effect on employee performance, training also has a very positive effect on employee performance, so that it is obtained from the training that has been implemented, employee performance has increased, as evidenced by an increase in the quality of employee work to be better, employees are more responsible for their work, and employees can improve their work ethic.